Efektivitas Aplikasi Proteus dalam Meningkatkan Hasil Belajar Rangkaian Listrik Siswa SMK - Tiara Putri Damayanti; Ihtiari Prastyaningrum (Jurnal Pendidikan dan Ilmu Fisika, 2026)
Learning about electrical circuits in vocational high schools is often hindered by students’ limited ability to apply concepts to circuit simulations and analysis. This study aims to determine the effectiveness of using the Proteus application in improving students’ cognitive learning outcomes at SMKN 1 Jiwan. This study employed a quantitative approach with a One-Group Pretest–Posttest design. The test instrument consisted of 10 multiple-choice items (valid and reliable) that measured students’ understanding of series, parallel, and mixed circuit concepts, as well as their ability to analyze and simulate electrical circuits. The final posttest score was an integration of the written test results and a 5-minute timed case study practical test. The data were analyzed using the N-Gain test. The results showed that the use of the Proteus application effectively improved cognitive learning outcomes, with an N-Gain value of 0.5076 (moderate category). Analysis by content indicator revealed the highest improvement in the mixed circuit material, while the lowest improvement occurred in the series circuit material, which was influenced by the ceiling effect. These findings confirm that the Proteus application is an interactive learning medium capable of facilitating concrete visualization for vocational high school students